Performance and Analysis of Reactive Power Compensation by Unified Power Flow Controller - Yogita Kumari; Anmol Gupta; Shiv Prakash Bihari; R.N. Chaubey; B. Sehgal (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
The Unified Power Flow Controller (UPFC) is the most versatile of the FACTS controllers envisaged so far. The main function of the UPFC is to control the flow of real and reactive power by injection of a voltage in series with the transmission line. Both the magnitude and the phase angle of the voltage can be varied independently. Real and Reactive power flow control can allow for power flow in prescribed routes, loading of transmission lines close to their thermal limits and can be utilized for improving transient and small signal stability of the power system. In this paper UPFC is incorporated in a SMIB (Single Machine Infinite Bus) system and the response of SMIB system has been recorded with and without UPFC, thereafter the comparison of both the output has been done. When no UPFC is installed, real and reactive power through the transmission line cannot be controlled. This paper presents control and performance of UPFC intended for installation on that transmission line to control power flow. Installing the UPFC makes it possible to control amount of active power flowing through the line. Simulations are carried out using MATLAB software to validate the performance of the UPFC.